2013
DOI: 10.1364/boe.4.002383
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of lung structures from optical coherence tomography images

Abstract: Abstract:Characterization of the size of lung structures can aid in the assessment of a range of respiratory diseases. In this paper, we present a fully automated segmentation and quantification algorithm for the delineation of large numbers of lung structures in optical coherence tomography images, and the characterization of their size using the stereological measure of median chord length. We demonstrate this algorithm on scans acquired with OCT needle probes in fresh, ex vivo tissues from two healthy anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Meissner et al demonstrated the feasibility of the segmentation and quantification of alveoli with OCT [52]. Pagnozzi et al demonstrated the automated quantification of lung structure using OCT with a fiber needle probe [53].…”
Section: Uhr-oct Imaging Of Rat Lungmentioning
confidence: 99%
“…Meissner et al demonstrated the feasibility of the segmentation and quantification of alveoli with OCT [52]. Pagnozzi et al demonstrated the automated quantification of lung structure using OCT with a fiber needle probe [53].…”
Section: Uhr-oct Imaging Of Rat Lungmentioning
confidence: 99%
“…Similar to many imaging modalities, limitations based on reproducibility and reliability of both the technique and analysis of images are being studied and improved. 97,98 The widespread availability of flexible bronchoscopy in combination with early translational success might result in an adoption of these modalities into clinical care practices in the next 5 years.…”
Section: Bronchoscopy Applicationsmentioning
confidence: 99%
“…The fetal lamb lung volume has been cropped so as to reveal the bifurcation of two bronchioles. Recent work has seen the application of automated quantification algorithms to analyze such volumetric data and compute stereological measures of the air space dimensions (100). The result of one such algorithm is shown in FIGURE 3E, with the air spaces delineated in green.…”
Section: Alveolar Imagingmentioning
confidence: 99%